THE ROLE OF TRAINING AND DEVELOPMENT OF GEN-Z EMPLOYEES IN IMPROVING SERVICE QUALITY AT PT JRX POOL & CAFÉ BANDUNG CITY - Muhammad Dadi Priadi; Inka Hermando Batubara; Hersusetiyati Hersusetiyati; Nurhaeni Sikki; Livy Putrikita Gemellia (PT. Altin Riset Publishing, 2025)
This study aims to analyze the role of training and development of Gen-Z employees in improving service quality at PT JRX Pool & Café. Employee training and development is a key factor in improving skills, work efficiency, and professionalism, especially for Gen-Z employees who have unique characteristics in the world of work. This research uses descriptive qualitative methods with data collection techniques through observation, interviews, and documentation. The results show that training at PT JRX Pool & Café is still limited, with only one implementation in the last three years, as well as retraining which is still in the planning stage. In addition, cross-functional training and creativity programs have not been formally implemented, although there are informal initiatives in some departments. In terms of development, the study found that performance evaluations are conducted regularly through self-assessment and supervisor appraisals. However, there are still challenges in work discipline, absenteeism, and employee initiative in contributing to service innovation. The service quality of Gen-Z employees at PT JRX Pool & Café is considered quite good, but there are still some obstacles in the aspects of reliability, responsiveness, and empathy towards customers. The conclusion of this study confirms that more structured and continuous training and development is urgently needed to improve service quality and customer satisfaction. Companies need to improve training methods to better suit Gen-Z characteristics, including technology-based approaches, real case simulations, and continuous evaluation to ensure service standards remain optimal.